Deutsch-russische Kulturbeziehungen im 20. Jahrhundert. Einflüsse und Wechselwirkungen - Möller, Horst; Cubar'jan, Aleksandr O. (Mitteilungen der Gemeinsamen Kommission für die Erforschung der jüngeren Geschichte der deutsch-russischen Beziehungen, 2023)
The sixth volume of the "Communications" of the German-Russian Historical Commission includes papers presented at the 2012 Hamburg Colloquium. Presented bilingually - as always - the fifteen essays by prominent German and Russian historians and cultural scholars examine a broad range of cultural interactions between Germany and Russia.